Ocular Surface Symptoms in Veterans Returning From Operation Iraqi Freedom and Operation Enduring Freedom - Modi, Yasha S. (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE. To correlate situational exposures and psychiatric disease with self-reported ocular surface symptoms in a younger veteran population involved in Operation Iraqi Freedom and Operation Enduring Freedom (OIF/OEF). METHODS. Cross-sectional study of all veterans evaluated in the OIF/OEF clinic between December 2012 and April 2013 who completed the dry eye questionnaire and screening evaluations for environmental exposures, posttraumatic stress disorder (PTSD), and depression. The main outcome measures were the influence of environmental exposure and psychiatric disease on ocular surface symptoms. RESULTS. Of 115 participants, the average age was 33 years. While overseas, exposure to incinerated waste (odds ratio [OR] 2.67, 95% confidence interval [CI] 1.23–5.81, P = 0.02) and PTSD (OR 2.68, 95% CI 1.23–5.85, P = 0.02) were associated with self-reported ocular surface symptoms. On return to the United States, older age (OR per decade 2.66, 95% CI 1.65–4.31, P = 0.04) was associated with persistent symptoms and incinerated waste was associated with resolution of symptoms (OR 0.25, 95% CI 0.07–0.90, P = 0.04). When evaluating symptom severity, 26% of the responders complained of severe ocular surface symptoms, with PTSD (OR 3.10, 95% CI 1.22–7.88, P = 0.02) and depression (OR 4.28, 95% CI 1.71–10.68, P = 0.002) being significant risk factors for their presence. CONCLUSIONS. PTSD was significantly associated with ocular surface symptoms both abroad and on return to the United States, whereas air pollution in the form of incinerated waste, was correlated with reversible symptoms.